2012
DOI: 10.3855/jidc.2082
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of virulence factors in diarrhoeagenic Escherichia coli isolates from children in Nairobi, Kenya.

Abstract: Introduction: Among the bacterial causes, diarrheagenic Escherichia coli (DEC) is the most important etiologic agent of childhood diarrhoea and represents a major public health problem in developing countries. New evidence suggests that major differences in virulence among groups of DEC pathotypes may be related to the presence of specific pathogenicity islands (PAIs). Methodology: Multiplex and conventional PCR assays were used to identify the DEC pathotypes and PAIs respectively from 207 E. coli isolates. Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
16
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 26 publications
(24 reference statements)
4
16
1
Order By: Relevance
“…On the other hand, EPEC and STEC were detected more frequently in children less than 5 years of age but ETEC and EIEC were isolated from children of 6–10 years of age. Several studies with stool samples from children under five showed similar results to the ones demonstrated in our study (Franzolin et al, 2005; Amisano et al, 2011; Makobe et al, 2012). Whereas, the frequency of DAEC strains in our study was in general low, DAEC strains have been recovered frequently from adults with diarrhea in Brazil (Mansan-Almeida et al, 2013).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…On the other hand, EPEC and STEC were detected more frequently in children less than 5 years of age but ETEC and EIEC were isolated from children of 6–10 years of age. Several studies with stool samples from children under five showed similar results to the ones demonstrated in our study (Franzolin et al, 2005; Amisano et al, 2011; Makobe et al, 2012). Whereas, the frequency of DAEC strains in our study was in general low, DAEC strains have been recovered frequently from adults with diarrhea in Brazil (Mansan-Almeida et al, 2013).…”
Section: Discussionsupporting
confidence: 91%
“…In addition, we identified DAEC, STEC and observed a very low frequency of EIEC. Previous studies from Kenya and Brazil reported similar findings in children (diarrhea) with prevalence of less than 1% for STEC and EIEC (Franzolin et al, 2005; Makobe et al, 2012). All STEC strains identified in this study were negative for the O157:H7 serotype.…”
Section: Discussionsupporting
confidence: 71%
“…nteropathogenic Escherichia coli (EPEC) is a human pathogen that causes infantile diarrhea in developing countries (1)(2)(3)(4)(5)(6)(7). EPEC adheres to host intestinal epithelium and induces attaching and effacing (A/E) lesions, which are characterized by intimate attachment of the organisms to host epithelial cells and effacement of the surrounding enterocyte microvilli (8).…”
mentioning
confidence: 99%
“…Application of PCR methods allows identification of all known Afa/Dr adhesins [18,19]. the F1845 gene probe) consisting of a 390-bp polynucleotide fragment from the daaC gene, which encodes a molecular usher necessary for expression of the F1845 fimbriae, enables detection of about 75% of DAEC strains.…”
Section: Detectionmentioning
confidence: 99%